2008
DOI: 10.1007/s12088-008-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional and safety aspects of enterococci in dairy foods

Abstract: The genus Enterococcus like other LAB has also been featured in dairy industry for decades due to its specifi c biochemical traits such as lipolysis, proteolysis, and citrate breakdown, hence contributing typical taste and fl avor to the dairy foods. Furthermore, the production of bacteriocins by enterococci (enterocins) is well documented. These technological applications have led to propose enterococci as adjunct starters or protective cultures in fermented foods. Moreover, enterococci are nowadays promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 83 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…However recent studies have shown that E. faecalis and some lactic acid bacteria species can cause clinical infections, especially infective endocarditis. E. faecalis can be found not only in human and animal faeces but also on plants and this largely reduces it's usage as a sanitation indicator (Foulquié Moreno et al, 2006;Giraffa, 2003;Kaleli & DurluOzkaya, 2000;Bhardwaj et al, 2008).…”
Section: B Breve B Infantis B Thermophilum B Adolescentis B mentioning
confidence: 99%
“…However recent studies have shown that E. faecalis and some lactic acid bacteria species can cause clinical infections, especially infective endocarditis. E. faecalis can be found not only in human and animal faeces but also on plants and this largely reduces it's usage as a sanitation indicator (Foulquié Moreno et al, 2006;Giraffa, 2003;Kaleli & DurluOzkaya, 2000;Bhardwaj et al, 2008).…”
Section: B Breve B Infantis B Thermophilum B Adolescentis B mentioning
confidence: 99%
“…Probiotic bacteria Lactobacillus and Bacillus subtilis have been successfully applied to livestock species (Abdelqader et al, 2013). These two strains benefit animals by suppressing pathogens directly or indirectly (Bhardwaj et al, 2008;Seidavi et al, 2017). However, single species often expose limited functionality, leading to instability in aspects of the using effect (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the probiotic bacteria Lactobacillus (Sohail et al 2010) and Bacillus subtilis (Abdelqader et al 2013) have been applied to birds. The two strains benefit animals by suppressing pathogens directly or indirectly and reduce the occurrence of diseases (Tsaruk'ianova & Smirnova 2005;Bhardwaj et al 2008). But single species often exposed limited functionality, which led to instability in the aspect of using effect.…”
Section: Introductionmentioning
confidence: 99%